Guilt and the Transformation of Christian-Jewish Relations - von Kellenbach, Katharina (Studies in Christian-Jewish Relations, 2020)
While many church bodies condemned race-based antisemitism, both during and immediately after the Holocaust, the repudiation of theological anti-Judaism (e.g., the deicide charge and supersessionism) and renunciation of anti-Jewish writings by prominent theologians (e.g., Luther) required decades of intense study and negotiation. In Germany, in particular, activists in the Jewish-Christian dialogue understand the destruction of Jewish religious life in Europe as a turning point in Christian teachings on the Jewish future. In Dresden, for instance, the campaign to rebuild the destroyed Frauenkirche was tied to the construction of a new Jewish synagogue as a penitential act of restitution.